2017
DOI: 10.1038/s41598-017-05863-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Changes in the Power Distribution in Resting-State Brain Networks Associated with Pure Conduct Disorder

Abstract: Conduct disorder (CD) is a psychiatric disorder in children and adolescence. To investigate changes in the power distribution in brain networks between CD and typically developing (TD) groups, resting-state functional magnetic resonance imaging (rsfMRI) data of thirty-six subjects were first recorded, and then the data were preprocessed using DPARSF and SPM8. Meanwhile, the power of the blood oxygenation level-dependent (BOLD) signals of ninety brain regions was acquired using the integral of the Welch power s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…To our knowledge, no previously published rs-fMRI studies of CD have included female subjects ( Lu et al, 2015 , 2017 ; Zhou et al, 2015 , 2016 ; Pu et al, 2017 ; Wu et al, 2017 ; Zhang et al, 2017 ), let alone explored rs-fMRI gender differences in CD. In this study, we applied ALFF and fALFF to compare spontaneous brain activity between males and females with CD.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, no previously published rs-fMRI studies of CD have included female subjects ( Lu et al, 2015 , 2017 ; Zhou et al, 2015 , 2016 ; Pu et al, 2017 ; Wu et al, 2017 ; Zhang et al, 2017 ), let alone explored rs-fMRI gender differences in CD. In this study, we applied ALFF and fALFF to compare spontaneous brain activity between males and females with CD.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, superior longitudinal fasciculus areas were shown to have differences in diffusion measurements that suggested poor maturation of structural connections (Hummer et al, 2015) in children with DBDs. Morphological aberrance of frontoparietal (Zhang et al, 2017;Cao et al, 2018) and temporal gyrus areas can lead to disruptive behavior (Huebner et al, 2008;Hyatt et al, 2012;Fairchild et al, 2015) and most of these regions were found to be class discriminative in this study. Functional connectivity alterations have been reported for children with DBDs, and class discriminative regions found using grad-CAM were consistent with many of the reported regions (Lu et al, 2015;Werhahn et al, 2020).…”
Section: Discussionmentioning
confidence: 52%